Quantitative live imaging of endogenous DNA replication in mammalian cells. - Andrew Burgess; Thierry Lorca; Anna Castro (PLoS ONE, 2012)
Historically, the analysis of DNA replication in mammalian tissue culture cells has been limited to static time points, and the use of nucleoside analogues to pulse-label replicating DNA. Here we characterize for the first time a novel Chromobody cell line that specifically labels endogenous PCNA. By combining this with high-resolution confocal time-lapse microscopy, and with a simplified analysis workflow, we were able to produce highly detailed, reproducible, quantitative 4D data on endogenous DNA replication. The increased resolution allowed accurate classification and segregation of S phase into early-, mid-, and late-stages based on the unique subcellular localization of endogenous PCNA. Surprisingly, this localization was slightly but significantly different from previous studies, which utilized over-expressed GFP tagged forms of PCNA. Finally, low dose exposure to Hydroxyurea caused the loss of mid- and late-S phase localization patterns of endogenous PCNA, despite cells eventually completing S phase. Taken together, these results indicate that this simplified method can be used to accurately identify and quantify DNA replication under multiple and various experimental conditions.